Η χρήση του υδρογόνου ως πρόσθετο καύσιμο σε μηχανές εσωτερικής καύσης που λειτουργούν με μείγμα βιοντίζελ και πετρελαίου - Βραχνού, Γιάννης (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
In recent years, as it is well known, the changes in the global climate and the environmental pollution have awaked the global scientific community and not only. Damages resulting from the intensity of extreme weather events, the rice in average global temperature, the corrosive effect of acid rain, desertification issues and soil exposure due to prolonged drought periods and the fact that the polar ice caps are melting faster than predicted, are the evidences of the environmental crime taking place nowadays. The main culprit of this environmental crime appears to be the excessive use of fossil fuels as an easy and economical solution to meet the world's energy needs. The energy crisis of 1973 led to the deterioration of energy problems. Due to the energy problem which is even more intense today and the reserves of the fossil fuels that are expected to be exhausted within the next years, people should turn their attention to other energy sources or carries. There are solutions to avoid the impending environmental doom. Researches put already the alternative solutions under the microscope and now huge sums of money are being lend to universities and research centers on research aimed to become truly independent of the fossil fuels. Alongside the transitional technologies where disagreement exists, all scientists agree on the same solution. The "hydrogen economy" is the most likely to succeed the current one, the economy of "black gold". It appears, therefore, that hydrogen, which is the basis of the universe and which is abundant in nature but bound to other molecules, is one of the most popular candidates to meet the energy demand of the global community. Hydrogen has already penetrated in the automotive market, as a main fuel in Internal Combustion Engines (ICE). Hydrogen is in widespread use by the global energy community. In fuel-cell conversion, the hydrogen is turned into electricity through fuel cells to power the motors. Moreover, for diesel engines and vehicles, biodiesel has done its emergence, the use of which is an innovation in the present Thesis. Biodiesel is a biofuel that is derived from biological materials, such as plants and is one of the new fuels that the U.S. based on that could one day reduce its energy dependence on the Middle East. Biodiesel, that has not even existed ten years ago, has been presented to the U.S. Department of Energy statistics called "yellow grease". In this thesis is examined theoretically and experimentally the use of hydrogen as a fuel additive in Internal Combustion Engines (ICE) operating with a mixture of diesel and biodiesel in different proportions. The purpose is to improve combustion, reduce consumption of fossil fuels and simultaneously reduce emissions of sulfur dioxide (SO2), carbon monoxide (CO), carbon dioxide (CO2), particulate matter (PM) and unburned hydrocarbons (HCs). Hydrogen is generated through the electrolysis of water and is not stored but produced on demand. Hydrogen is used in the engine as a fuel additive so the engines do not have to be built from scratch, but it can be fed into existing engines.
Keywords: Hydrogen; Biodiesel; Energy source; Υδρογόνο; Βιοντίζελ; Ηλεκτρογεννήτρια